Cover Image. (28th March 2019) - Zhou, Jiqiong; Wilson, Gail W.T.; Cobb, Adam B.; Yang, Gaowen; Zhang, Yingjun
Abstract : The cover image is based on the Research Article Phosphorus and mowing improve native alfalfa establishment, facilitating restoration of grassland productivity and diversity, by Jiqiong Zhou et al., https://doi.org/10.1002/ldr.3251 .